Endothelial Microvesicles Induce Pulmonary Vascular Leakage and Lung Injury During Sepsis - Zheng, Danyang; Zhang, Jie; Zhang, Zisen; Kuang, Lei; Zhu, Yu; Wu, Yue; Xue, Mingying; Zhao, Hongliang; Duan, Chenyang; Liu, Liangming; Li, Tao (Frontiers in Cell and Developmental Biology, 2020)
Sepsis is a prevalent severe syndrome in clinic. Vascular leakage and lung injury are important pathophysiological processes during sepsis, but the mechanism remains obscure. Microvesicles (MVs) play an essential role in many diseases, while whether MVs participates in vascular leakage and lung injury during sepsis is unknown. Using cecal ligation and puncture induced sepsis rats and lipopolysaccharide stimulated vascular endothelial cells (VECs), the role and the underlying mechanism of endothelial microvesicles (EMVs) in pulmonary vascular leakage and lung injury in rats were observed. The role of MVs from sepsis patients was verified. The results showed that the concentration of MVs in blood was significantly increased after sepsis. MVs from sepsis rats and patients induced apparent pulmonary vascular leakage and lung injury, among which EMVs played the dominant role, in which miR-23b was the key inducing factor in vascular leakage. Furthermore, by knockdown and overexpression of miR-23b in EMVs showing that miR-23b mainly targeting on ZO-1to induce vascular leakage.MVs from sepsis patients induced pulmonary vascular leakage and lung injury in normal rats. Application of classic antidepressants amitriptyline reduced the secretion 5 of EMVs, and alleviated vascular leakage and lung injury. The study suggests that EMVs play an important role in pulmonary vascular leakage and lung injury during sepsis by transferring functional miR-23b. Antagonizing the secretion of EMVs and its miR-23b might be a potential target for the treatment of severe sepsis.